2005
DOI: 10.1079/ivp2005644
|View full text |Cite
|
Sign up to set email alerts
|

Efficient plant regeneration through direct somatic embryogenesis from leaf explants of Phalaenopsis ‘Little Steve’

Abstract: SummaryLeaf segments of the orchid sp. Phalaenopsis 'Little Steve' were used as explants testing the effects of 2,4-dichlorophenoxyacetic acid (2,4-D; 0.45, 2.26, 4.52 mM), 6-furfurylaminopurine (kinetin; 2.32, 4.65, 13.95 mM), N 6 -benzyladenine (BA; 2.22, 4.44, 13.32 mM), and 1-phenyl-3-(1,2,3-thiadiazol-5-yl)-urea (TDZ; 2.27, 4.54, 13.62 mM) on the induction of direct somatic embryogenesis. After 20 -30 d of culture in darkness, clusters of somatic embryos formed from leaf surfaces and wounded regions of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 17 publications
(14 reference statements)
5
46
0
7
Order By: Relevance
“…62,63 Researchers have also demonstrated that auxin can inhibit cytokinin-induced direct somatic embryogenesis in Phalaenopsis and Oncidium species. 64,65 Overall, these findings suggest that high exogenous auxin levels promote and/or maintain undifferentiated growth, while hormonedepleted media or lower levels of auxin in conjunction with cytokinins typically produce PLBs from callus. This conclusion further supports the premise that, in vivo, uniform auxin distribution helps to maintain a dedifferentiated protocorm until auxin is redirected to appropriate locations and is present in precise concentrations to help stimulate differentiation (Fig.…”
Section: Protocorm Like-bodies (Plbs)mentioning
confidence: 90%
“…62,63 Researchers have also demonstrated that auxin can inhibit cytokinin-induced direct somatic embryogenesis in Phalaenopsis and Oncidium species. 64,65 Overall, these findings suggest that high exogenous auxin levels promote and/or maintain undifferentiated growth, while hormonedepleted media or lower levels of auxin in conjunction with cytokinins typically produce PLBs from callus. This conclusion further supports the premise that, in vivo, uniform auxin distribution helps to maintain a dedifferentiated protocorm until auxin is redirected to appropriate locations and is present in precise concentrations to help stimulate differentiation (Fig.…”
Section: Protocorm Like-bodies (Plbs)mentioning
confidence: 90%
“…TDZ is a substituted phenyl urea with cytokinin-like activity (van Staden, Zažímalová, & George, 2008;Jitsopakul, Thammasiri, & Ishikawa, 2013). The ascendancy of TDZ in inducing somatic embryos (infant PLBs) from leaf explants was recounted in numerous orchid species including Oncidium (Mayer, Stancato, & Appezzato-Da-Glória, 2010), Doritaenopsis (Park, Yeung, Chakrabarty, & Paek, 2002), Dendrobium and Phalaenopsis (Kuo, Chen, & Chang, 2005). TDZ is also useful for rapid plant regeneration through organogenesis (Kishor & Devi, 2009;Jitsopakul, Thammasiri, & Ishikawa, 2013), somatic em-bryogenesis (Jheng, Do, Liauh, Chung, & Huang, 2006;Gow, Chen, & Chang, 2009), or PLB formation of orchids (Mayer, Stancato, & Appezzato-Da-Glória, 2010;Khoddamzadeh et al, 2011;Roy, Sajeev, Pattanayak, & Deka, 2012).…”
Section: Effect Of Pgrs On Embryogenic Callus Induction From Leaf Tipmentioning
confidence: 99%
“…Most of the time, callus developed at the cut ends of leaf tip explants, suggesting that the wounding might have triggered dedifferentiation of cells to form callus. Kuo, Chen, & Chang (2005) reported that the highest ability of Phalaenopsis leaf explants to form embryos was found at adaxial surfaces near cut ends on TDZ-containing medium. Figure 3C-D show that the callus masses composed of spherical, compact and loose aggregates of cells.…”
Section: Histology and Scanning Electron Microscope Observations On Ementioning
confidence: 99%
See 1 more Smart Citation
“…Proliferasi kalus dilakukan pada enam komposisi media, yaitu Pro-D1 (ID-1 + 10% air kelapa) ( (Kuo et al 2005). Kalus diproliferasi dalam erlenmeyer 100 ml (Pyrex IWAKI TE-32, Indonesia) dengan kepadatan 1 g kalus/25 ml media.…”
Section: Pengaruh Media Dan Periode Subkultur Terhadap Proliferasi Kaunclassified